Effect of torrefaction and fractional condensation on the quality of bio-oil from biomass pyrolysis for fuel applications. (15th March 2022) - Valizadeh, Soheil; Oh, Daejun; Jae, Jungho; Pyo, Sumin; Jang, Hoyeon; Yim, Hyeonji; Rhee, Gwang Hoon; Khan, Moonis Ali; Jeon, Byong-Hun; Lin, Kun-Yi Andrew; Show, Pau Loke; Sohn, Jung Min; et al.
Graphical abstract: Highlights: Woody sawdust pyrolysis was performed to produce phenolic-rich bio-oil. Raising temperature increased phenolics, while decreased acids. Torrefaction increased the production of phenolics at the expense of oxygenates. Fractional condensation effectively separated phenolics from harmful content. Synergetic effects of torrefaction and fractional condensation were demonstrated. Abstract: This study evaluated the effects of the pyrolytic temperature, torrefaction, and fractional condensation alongside the combined efficiency of torrefaction and fractional condensation on the production of high-quality bio-oil from woody sawdust (WS) pyrolysis for the first time. The proportion of acids decreased gradually with increasing temperature from 300 to 600 °C, while the selectivity of phenolic compounds was enhanced. An increase in the torrefaction severity caused a significant decrease in the bio-oil yield at the pyrolysis stage but favorably increased the selectivity of phenolics and mitigated the fraction of oxygenated compounds. In fractional condensation, the proportion of total oxygenates was increased with decreasing condensing temperature from the first condenser (Con 1) (250 °C) to the fourth condenser (Con 4) (-20 °C). On the other hand, most phenolics were condensed in Con 1 and then showed a decreasing trend with a decrease in temperature. Integrating torrefaction and fractional condensation decreased the oxygenated content dramatically while increasing the selectivity of phenolic content significantly (up to 89.48%) under high- and mild- temperatures condensation, suggesting a functional improvement. Overall, the torrefaction of biomass combined with fractional condensation in biomass pyrolysis is a promising approach to produce biofuels.